2018
DOI: 10.1088/1361-6579/aad902
|View full text |Cite
|
Sign up to set email alerts
|

Cuffless blood-pressure estimation method using a heart-rate variability-derived parameter

Abstract: The results of the current study demonstrate that the inclusion of factors associated with autonomic activities in the BP estimation model would improve the BP estimation accuracy, especially for hypertensive subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…M1 is the modality with the most data points and the strongest r. M1 is also the only category to include studies with sample sizes over 30, making the correlations stronger than those of studies with small sample sizes. Across most modalities, SBP estimations have consistently higher correlations with real SBP than DBP estimations do with real DBP [17,21,23,25,27,40,43,44,51,52,55,60,61,65,81,82]. Three studies from M2 [15], M1 [59], and M1 [67] showed the opposite trend and two studies from M1 [31] and M4 [20] reported the same r for both SBP and DBP.…”
Section: Global Distribution and Combinations Of Biosignals Used In Lmentioning
confidence: 89%
See 4 more Smart Citations
“…M1 is the modality with the most data points and the strongest r. M1 is also the only category to include studies with sample sizes over 30, making the correlations stronger than those of studies with small sample sizes. Across most modalities, SBP estimations have consistently higher correlations with real SBP than DBP estimations do with real DBP [17,21,23,25,27,40,43,44,51,52,55,60,61,65,81,82]. Three studies from M2 [15], M1 [59], and M1 [67] showed the opposite trend and two studies from M1 [31] and M4 [20] reported the same r for both SBP and DBP.…”
Section: Global Distribution and Combinations Of Biosignals Used In Lmentioning
confidence: 89%
“…For example, Wang et al [38] showed a significant correlation between HR and BP and demonstrated that the addition of both HR and previous BP measurements to the PTT-BP estimation significantly improved the error (p < 0.05). Other measurements such as PIR have been incorporated into the PTT-BP estimation [16,51,67,69,71,78,82] as it reflects the low-frequency component of arterial diameter changes, which are not normally picked up by conventional PTT measurements. Here, PIR is measured as the ratio of minimum to maximum amplitudes of a PPG waveform in one cardiac cycle.…”
Section: Accuracy Of Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations